Positive effect of combined exercise training in a model of metabolic syndrome and menopause: Autonomic, inflammatory, and oxidative stress evaluations - Conti, Filipe Fernandes (2015)
It is now well established that after menopause cardiometabolic disorders become more common. Recently, resistance exercise has been recommended as a complement to aerobic (combined training, CT) for the treatment of cardiometabolic diseases. The aim of this study was to evaluate the effects of CT in hypertensive ovariectomized rats undergoing fructose overload in blood pressure variability (BPV), inflammation, and oxidative stress parameters. Female rats were divided into the following groups (n = 8/group): sedentary normotensive Wistarrats (C), and sedentary (FHO) or trained (FHOT) ovariectomized spontaneously hypertensive rats undergoing and fructose overload. CT was performed on a treadmill and ladder adapted to rats in alternate days (8 wk; 40-60% maximal capacity). Arterial pressure (AP) was directly measured. Oxidative stress and inflammation were measured on cardiac and renal tissues. The association of risk factors (hypertension + ovariectomy + fructose) promoted increase in insulin resistance, mean AP (FHO: 174 ± 4 vs. C: 108 ± 1 mmHg), heart rate (FHO: 403 ± 12 vs. C: 352 ± 11 beats/min), BPV, cardiac inflammation (tumor necrosis factor-a-FHO: 65.8 ± 9.9 vs. C: 23.3 ± 4.3 pg/mg protein), and oxidative stress cardiac and renal tissues. However, CT was able to reduce mean AP (FHOT: 158 ± 4 mmHg), heart rate (FHOT: 303 ± 5 beats/min), insulin resistance, and sympathetic modulation. Moreover, the trained rats presented increased nitric oxide bioavailability, reduced tumor necrosis factor-a (FHOT: 33.1 ± 4.9 pg/mg protein), increased IL-10 in cardiac tissue and reduced lipoperoxidation, and increased antioxidant defenses in cardiac and renal tissues. In conclusion, the association of risk factors promoted an additional impairment in metabolic, cardiovascular, autonomic, inflammatory, and oxidative stress parameters and combined exercise training was able to attenuate these dysfunctions..